On the mechanisms of shrinkage reducing admixture in alkali activated slag binders. (15th September 2022) - Al Makhadmeh, W.; Soliman, A.
Abstract: Shrinkage-reducing admixture (SRA) efficiency as a shrinkage mitigation technique has been proven for the alkali-activated slag (AAS) system. However, the controlling mechanism is a debatable subject. Moreover, it has been reported that SRA may retard strength development and slag hydration. Hence, this study explores the behaviour of SRA and its interactions with AAS's pore solution and systems. It showed that SRA affected AAS similarly to ordinary Portland cement (OPC), reducing pore solution's surface tension and maintaining a high internal relative humidity level. However, the critical micelle concentration of SRA (i.e. 9%) was identified beyond which it self-aggregated in the bulk solution, reducing its efficiency. Chemical analysis of the extracted AAS pore solution showed how the presence of SRA impacted the aqueous electrolyte AAS pore solution. Besides, SRA reduced the dissolution affinity of ions (i.e. the cation/anion concentrations), retarding the hydration reaction and extending the setting time. Nuclear magnetic resonance results confirmed that SRA addition lowered the polymerisation degree for C-A-S-H, thereby reducing shrinkage driven by C-A-S-H syneresis. The findings of this study highlighted the critical roles of AAS pore solution composition and the formation of hydration products in the presence of SRA on AAS shrinkage behaviour and the development of other properties. Highlights: SRA concentration at a level less than the CMC, significantly mitigated the autogenous shrinkage of AAS. The chemical analysis showed that there is a strong interaction between SRA and AAS pore solution. The presence of SRA to AAS led to the formation of solid species with a shorter MCL. SRA addition reduced the syneresis effect of C-A-S-H gels and enhanced the stability of the microstructure.